It (2017) [videorecording (DVD)] - Skarsgård, Bill; Martell, Jaeden; Wolfhard, Finn, 2002-; King, Stephen, 1947- (Warner Bros. Home Entertainment, 2018)
A group of bullied kids band together when a monster, taking the appearance of a clown, begins hunting children.